Quality of life and its determinants in students of medical and non-medical education - Ameer, Muhammad H.; Khalid, Noman; Asghar, Saad (International Journal Of Community Medicine And Public Health, 2020)
Background: This study was conducted to find and compare the quality of life of medical and non-medical students using a WHO questionnaire. Methods: The cross-sectional study was conducted at Shaikh Khalifa Bin Zayed Al-Nahyan Medical and Dental College, University of the Punjab and University of Engineering and Technology (UET) Lahore. The shortened version of WHO Quality of Life questionnaire was used. Consecutive non-probability sampling was utilized to collect data which was analysed using SPSS 21. Results: Of the 450 questionnaires distributed, 400 qualified for the analysis. Out of 200 medical students’ questionnaires, 118 were filled by male and 82 by female medical students. The mean age of medical students participating in this study was 20.425±1.498 years. Of the 200 qualified non-medical questionnaires, 111 were filled by male and 89 by female non-medical students. The mean age of non-medical students was 20.995±1.645 years. Medical students’ environmental domain showed the highest mean score 65.52±14.82 followed by social relationships 62.39±13.98, psychological domain 59.84±13.64 and physical health domain 54.89±12.03. Non-medical students’ environmental domain had the highest mean score 64.18±15.67 followed by psychological domain 62.45±13.62, social relationships domain 59.82±14.42 and physical health domain 57.04±12.98. The scores of four domains were found to be significantly different in both disciplines (medical education and non-medical education). Conclusions: The results of present study emphasize on the need to look into all the parameters of physical health, psychological health, social relationships and environment of medical and non-medical institutes to improve the quality of life of students.